Organizing Activities for Chemistry Pedagogy Students to Research and Practice Extracting Cajeput Essential Oils from Melaleuca Leaves Using the CDIO Approach (Journal of Contemporary Educational Policies and Practices, 2024)
The philosophy in teacher training is geared towards students' excitement and passion for what the teacher will do in the role of the "Soul Engineer" in high schools. That philosophy in the CDIO approach is in the direction of developing the core competencies for graduates, Conceive - Design - Implement – Operate the teaching and educational process in the context of school educational innovation towards standardization, modernization, socialization, democratization and international integration. With the goal of researching the process of organizing the teaching of practical chemical experiments based on the CDIO standards to develop experimental competence for chemistry pedagogical students, the authors used an experimental method through instructing students to extract cajuput essential oil and implementing 14 teaching activities with this experiment. Drawing on the CDIO-based teaching standards, we have built a practical chemistry process to form and develop the competencies for students in chemistry pedagogy. Based on that process, we organized teaching activities and experimented with: (1) Extracting cajeput essential oil by the steam attraction method; (2) The process of preparing an antiseptic solution supplementing the extracted pure cajeput essential oil. The experimental data confirms that the CDIO teaching model applies effectively to chemistry practical exercises for pedagogical students.